Innovation and Price Competition in a Two-Sided Market - LIN, Mei (Institutional Knowledge at Singapore Management University, 2011)
We examine a platform's optimal two-sided pricing strategy while considering seller-side innovation decisions and price competition. We model the innovation race among sellers in both finite and infinite horizons. In the finite case, we analytically show that the platform's optimal seller-side access fee fully extracts the sellers' surplus, and that the optimal buyer-side access fee mitigates price competition among sellers. The platform's optimal strategy may be to charge or subsidize buyers depending on the degree of variation in the buyers' willingness to pay for quality; this optimal strategy induces full participation on both sides. Furthermore, a wider quality gap among sellers' products lowers the optimal buyer-side fee but leads to a higher optimal seller-side fee. In the infinite innovation race, we perform computations to find the stationary Markov equilibrium of sellers' innovation rate. Our results show that when all sellers innovate, there exists a parameterization under which a higher seller-side access fee stimulates innovation.